The impact of lemon aromateraphy and breath relaxation in blood pressure on hypertensive elderly at Patukan Gamping Sleman Yogyakarta - Ana Apriana Murtianingsih; Edy Suprayitno (International Journal of Health Science and Technology, 2019)
Hypertension is defined as the increase of chronicle blood pressure that is usually happened on elderly people. Hypertension belongs to one of Cardiovascular Disease (CVD) that becomes the cause of 80% mortality in Indonesia. One of non-pharmacological medical treatment for hypertension was by using the lemon aromatic therapy and inner relaxation breath. This therapy aims to give calming and comforting effect that leads to the decrease of heart performance and blood pressure.To find out the impact of lemon aromatic therapy and inner breath relaxation toward blood pressure on elderly people’s hypertension. This research belongs to Quasy Experiment Research Design by implementing Non Equivalent Control Groupwith one treatment group and one controlled group. This research implemented total sampling technique with 22 respondents in total. The mann-whitneystatistical analysis showed that p value 0,000 of the diastole blood pressure was at 0,016 with trustworthiness at α 0,05. There is impact of lemon aromatic therapy and inner relaxation breath toward the decrease of blood pressure on the hypertension patient. The patient of hypertension is suggested to use lemon aromatic therapy and inner relaxation breath as one of non-pharmacological medical treatment that can reduce the high blood pressure.